“Nature’s Bastards”: Grafted Generation in Early Modern England - Duncan, Claire (Renaissance and Reformation / Renaissance et Réforme)

(untitled) (Iter Press, 2015)
This paper examines the shared rhetoric between human and horticultural generation in early modern England, particularly focusing on grafting. Early modern English gardening manuals imagine grafting as a method of controlling generation in the natural world, and early modern English obstetrical treatises imagine the female generative body in horticultural language. Alongside these scientific texts, this article uses Shakespeare’s The Winter’s Tale as a literary case study of grafting rhetoric. Ultimately, while grafting treatises imagine man’s power over generation in the natural world and obstetrical treatises imagine controlling human generation using horticultural metaphor, The Winter’s Tale complicates this fantasy by depicting Leontes’s efforts at genealogical control as unnecessary and fruitless: not only do Perdita and Hermione survive and flourish after his attempts to kill them, but Perdita is the legitimate and non-grafted offspring of Hermione and Leontes.